(untitled) - Gutta, Rajendra (Indianapolis, 2002)
Oracle DBA Automation Scripts shows you how to build the scripts that automate the daily operations of Oracle database management. These scripts will work in a variety of environments, including the Windows NT, Sun Solaris 2.x, Sun OS 5.x, HP-UX 11.x, and AIX 4.x operating systems. You'll learn the command differences between these operating systems and how to write scripts to integrate SQL with your OS. Whether you're an aspiring DBA or you have a few years under your belt, you'll be able to use the commands and scripts presented here to install, operate, manage, and tune Oracle databases.
Keywords: Oracle (computer file),Relational databases,Database management